Evaluación de la gestión energética en la fábrica de helados de bayamo - Albán Robayo, Geovanny Rodrigo (2016)
The Investigation was accomplished at Ice-creams factory of Bayamo, for the sake of evaluating this productive entity's energetic status. It was necessary to effect a quest of information about the energetic status of Cuba and of the world for the development of this research, that way I eat of the different models of energetic step that they apply over different countries. However, in order to determine the indicators of energetic step, it was necessary to apply the Energy's tools of Total Efficient Gestation’s Technology. Enter the principal results of this work they can indicate the following: Principal's areas I consume of electric power music the engine room and give it Preparation of Savors with a 80.4 %, I consume principal's energetic bearer in equivalent tons of oil the electric power went with a 97 %, the evaluated variables electric power and production present a weak correlation, right now than moral values the inferiors are R2 to 0.2 in the years 2013 and 2014. In addition, the evaluated variables electric power and production, in the year 2015 presented a loud correlation, since R2 value is 0.86, that considers itself acceptable.